ETHICAL CRITERIA OF ERGONOMICS IN MODERN SOCIETY: https://doi.org/10.5281/zenodo.15684964 - Kuramatov , Murod (Journal of Contemporary World Studies, 2025)
This article analyzes the ethical principles of ergonomics in modern society from both philosophical and practical perspectives. It explores the harmony between human beings and the work environment, the impact of technological tools on human health and values, and the ethical evaluation of ergonomic approaches based on comfort in labor processes and labor rights. The article also discusses the compatibility of ergonomic ethical principles with responsibility, justice, and humanism through socio-philosophical analysis. Based on statistical tables and real-life cases, conclusions are drawn regarding the ethical regulation of ergonomic principles.